2010
DOI: 10.1590/s1516-35982010001000021
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho e qualidade dos ovos de poedeiras comerciais alimentadas com rações contendo diferentes níveis de metionina e lisina

Abstract: RESUMO -Foram avaliados os efeitos dos níveis de metionina e lisina sobre o desempenho e a qualidade interna e externa dos ovos de poedeiras comerciais. Foram utilizadas 256 poedeiras Hisex White com 68 semanas de idade, alojadas individualmente em delineamento inteiramente casualizado em arranjo fatorial 4 × 4, com quatro níveis de lisina (0,482; 0,682; 0,882 e 1,082%) e metionina (0,225; 0,318; 0,411 e 0,505%), totalizando 16 dietas, cada uma com quatro repetições de quatro aves. O desempenho foi avaliado po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Increasing dietary digestible lysine levels have been previously studied (Silva et al, 2010;Jardim Filho et al, 2010) and the results indicated that higher lysine levels resulted in heavier eggs, higher albumen percentage (Jardim Filho et al, 2008;Schmidt et al, 2008;Silva et al, 2010;Jardim Filho et al, 2010), and higher yolk percentage (Schmidt et al, 2008;Rocha et al, 2009;Jardim Filho et al, 2010;Silva et al, 2010). Other authors found increased egg weight with 770 Methionine + cystine (g/kg) 6.9…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing dietary digestible lysine levels have been previously studied (Silva et al, 2010;Jardim Filho et al, 2010) and the results indicated that higher lysine levels resulted in heavier eggs, higher albumen percentage (Jardim Filho et al, 2008;Schmidt et al, 2008;Silva et al, 2010;Jardim Filho et al, 2010), and higher yolk percentage (Schmidt et al, 2008;Rocha et al, 2009;Jardim Filho et al, 2010;Silva et al, 2010). Other authors found increased egg weight with 770 Methionine + cystine (g/kg) 6.9…”
Section: Resultsmentioning
confidence: 99%
“…Other experiments showed that increasing the levels of digestible lysine of layer diets did not affect Haugh units (Jardim Filho et al, 2008;Schmidt et al, 2008;Matos et al, 2009;Rocha et al, 2009;Jardim Filho et al, 2010;Silva et al, 2010;), yolk index (Jardim Filho et al, 2008;Schmidt et al, 2008;Rocha et al, 2009;Jardim Filho et al, 2010), or total egg solids (Jardim Filho et al, 2008;Matos et al, 2009;Jardim Filho et al, 2010).…”
Section: Egg Quality Of Hens Fed Different Digestible Lysine and Argimentioning
confidence: 96%
“…one of the main roles of choline is to donate methyl radicals, as well as methionine (Silva et al, 2010). These features may explain the inferior live performance when both synthetic methionine and choline were replaced in the diet (VMAC)compared with broilers consuming the diet where choline chloride 60% (AC) was replaced.…”
Section: Dietary Supplementation Of Alternative Methionine and Cholinmentioning
confidence: 99%
“…For many years, the formulation of chicken feedwas based on the concept of crude protein, resulting in amino acid content above that required by animals (SILVA et al, 2010). As the production of synthetic amino acids has increased in the world, diets have started to be formulated with lower protein levels and increased amino acid levels according to broilers requirements.…”
Section: Introductionmentioning
confidence: 99%